ADAPTASI SOSIAL ETNIS SUNDA DI NAGARI KOTO BARU KECAMATAN X KOTO KABUPATEN TANAH DATAR SUMATERA BARAT - Jamal, Rido Arifin; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the social adaptation process of the Sundanese ethnicity with the community studied from social, economic and educational aspects as well as the interaction form of the Sundanese ethnicity in establishing relationships with the community in Nagari Koto Baru, X Koto District, Tanah Datar Regency, West Sumatra. To analyze the phenomena that exist, researchers use the theory from Talcott Parson, namely Structural Functional (AGIL) and the theory of the adaptation process according to Oberg (1960) through four stages, namely Honeymoon, Culture Shock, Recovery and Adjustment. This study used qualitative methods with observational data collection techniques, in-depth interviews and documentation. As for the determination of research subjects using purposive sampling with the number of informants seven people including the head of the association and the head of the jorong as key informants, 3 people of Sundanese ethnicity and 2 local people. Data processing techniques used are data reduction, data presentation and data conclusions. The results of the study show that the process of adaptation to the Sundanese ethnic community for each individual will require a different time. One form of integration that exists is mixed marriage, apart from that language differences become an obstacle in communicating with the local community. So it can be concluded that the Sundanese ethnic adaptation process can go well with the surrounding community and the interactions that are established must be maintained so that good relations can run in harmony and peace. Keywords: Adaptation, Interaction, Ethnicity